Teachers’ Status of GeoGebra Use in The Teaching of Geometric Transformation - Muzirah Musa, Yusmaliza Mamat, Munirah Ghazali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study investigates teachers’ perspectives towards the eventual use of GeoGebra as a tool to enhance the learning of Geometric Transformation. Study participants included 98 secondary mathematics teachers in a district of Northern Malaysia. A mixed-methods approach with closed-ended and open-ended questionnaires was employed in this study. Data analysis was performed descriptively and via thematic content analysis. The finding reveals that only 15.3% of teachers use GeoGebra in their mathematics classroom even though teachers are of the view that their students have difficulties in learning geometry, and the use of GeoGebra has been recommended by the Malaysian Mathematics Curriculum and provided in textbooks. Some challenges in using GeoGebra, including lack of competency, exposure, and experience in operating GeoGebra, facilities, and times constraints. It is recommended that module development and training programs should adequately provide teachers to use GeoGebra to teach effectively in Geometric Transformation.